Myelodysplastic syndrome with pseudoreticulocytosis - (:unkn) unknown (My University, 2005)
A patient with myelodysplastic syndrome (MDS) with refractory anemia who had marked reticulocytosis in the absence of hemolytic anemia and/or blood loss is reported. Erythrocyte survival test showed that more than 50% of the patient's reticulocytes were still present on day seven. This should be due to the prolongation of reticulocyte maturation in MDS, and is known as pseudoreticulocytosis. This phenomenon which mimicks hemolytic anemia is an unusual presentation of myelodysplastic syndrome, with only 7 patients with pseudoreticulocytosis being reported previously.
Keywords: Myelodysplastic syndrome; Pseudoreticulocytosis